Ocena częstości występowania składowych zespołu metabolicznego w grupie pacjentów ze stabilną dusznicą bolesną kwalifikowanych do planowej koronarografii = Assessment of frequency of components of metabolic syndrome in patients with stable angina qualified for planning angiography - Sawicka, Katarzyna; Kapłon, Marta; Łuczyk, Robert; Wawryniuk, Agnieszka (Journal of Education, Health and Sport, 2016)
Sawicka Katarzyna, Kapłon Marta, Łuczyk Robert, Wawryniuk Agnieszka. Ocena częstości występowania składowych zespołu metabolicznego w grupie pacjentów ze stabilną dusznicą bolesną kwalifikowanych do planowej koronarografii = Assessment of frequency of components of metabolic syndrome in patients with stable angina qualified for planning angiography. Journal of Education, Health and Sport. 2016;6(9):391-421. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.62069 http://ojs.ukw.edu.pl/index.php/johs/article/view/3848 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. Ocena częstości występowania składowych zespołu metabolicznego w grupie pacjentów ze stabilną dusznicą bolesną kwalifikowanych do planowej koronarografii Assessment of frequency of components of metabolic syndrome in patients with stable angina qualified for planning angiography Katarzyna Sawicka1, Marta Kapłon1, Robert Łuczyk1, Agnieszka Wawryniuk1 1Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 1Department of Internal Medicine with the Department of Internal Nursing, Faculty of Health Sciences, Medical University of Lublin Streszczenie Wstęp. Ze stabilną dusznicą bolesną wiąże się występowanie zespołu metabolicznego. Zespół metaboliczny to zbiór wzajemnie powiązanych czynników metabolicznych takich jak: upośledzona tolerancja glukozy, insulinooporność, hiperinsulinemia, otyłość, zaburzenia lipidowe, nadciśnienie tętnicze. Zespół ten stanowi główną przyczynę rozwoju chorób sercowo-naczyniowych o podłożu miażdżycowym i cukrzycy typu 2. Za rozwój zespołu metabolicznego odpowiedzialne są predyspozycje genetyczne oraz współdziałające czynniki środowiskowe, w tym brak aktywności fizycznej oraz wysokokaloryczna dieta [1]. Materiał i metoda badań. W niniejszej pracy posłużono się metodą sondażu diagnostycznego. Do gromadzenia informacji wykorzystano autorski kwestionariusz ankiety. Ankieta obejmowała 37 pytań, w tym 33 pytania zamknięte i 4 pytania półotwarte, w których istniała możliwość wpisania własnej odpowiedzi przez osoby ankietowane. Pytania pozwoliły na zebranie danych dotyczących cech demograficznych badanej populacji oraz ocenę zasobu wiedzy respondentów na temat poszczególnych składowych zespołu metabolicznego. Wyniki badań. 1. Uzyskane wyniki badań wskazują, że u 70% pacjentów ze stabilną dusznicą bolesną kwalifikowanych do planowej koronarografii występują składowe zespołu metabolicznego. 2. Istnieje zależność pomiędzy miejscem zamieszkania pacjenta, a występowaniem składowych zespołu metabolicznego: u osób mieszkających w mieście częściej występuje zespół metaboliczny. 3. Istnieje zależność pomiędzy stylem życia, a występowaniem składowych zespołu metabolicznego (u 54,5% ankietowanych, którzy prowadzą niezdrowy styl życia, istnieje problem występowania zespołu metabolicznego). 4. Nie istnieje zależność pomiędzy podejmowaniem aktywności fizycznej, a występowaniem składowych zespołu metabolicznego. 5. Nadciśnienie tętnicze jest najczęściej występującą składową zespołu metabolicznego wśród badanej populacji. 6. Osoby mieszkające w mieście częściej narażone są na występowanie zespołu metabolicznego niż mieszkańcy wsi. 7. Nie istnieje istotna statystycznie zależność pomiędzy paleniem papierosów i spożywaniem alkoholu, a występowaniem zespołu metabolicznego. 8. Występowanie zespołu metabolicznego stwierdzono równie często w grupie osób, które twierdziły, że odżywiają się zdrowo, jak i u tych, które nie prowadzą zdrowego stylu odżywiania. Słowa kluczowe: zespół metaboliczny, dusznica bolesna stabilna, koronarografia Summary Admission. With stable angina pectoris involves the metabolic syndrome. The metabolic syndrome is a collection of interrelated metabolic factors such as impaired glucose tolerance, insulin resistance, hyperinsulinemia, obesity, lipid disorders, hypertension. This team is the main cause of the development of cardiovascular disease atherosclerosis and type 2 diabetes for the development of the metabolic syndrome are responsible genetic predisposition and associated environmental factors, including a lack of physical activity and calorie diet [1]. Materials and methods of research. In this paper method was used diagnostic survey. To collect information used proprietary questionnaire. The survey consisted of 37 questions, including 33 closed questions and 4 semi-open questions in which it was possible to enter their own answers by the respondents. Questions allowed to collect data on the demographic characteristics of the study population and resource evaluation of respondents' knowledge about the individual components of the metabolic syndrome. Findings. 1. Results of the study indicate that 70% of patients with stable angina pectoris referred for elective coronary angiography are components of metabolic syndrome. 2. There is a relationship between the place of residence of the patient, and the presence of components of the metabolic syndrome: in people living in the city is more common metabolic syndrome. 3. There is a relationship between lifestyle and the presence of components of the metabolic syndrome (54.5% of respondents who lead an unhealthy lifestyle, there is a problem of occurrence of the metabolic syndrome). 4. There is no relationship between the taking of physical activity, and the presence of components of the metabolic syndrome. 5. Hypertension is the most common component of metabolic syndrome in the population studied. 6. If you live in the city often are exposed to metabolic syndrome than rural residents. 7. There is no statistically significant relationship between cigarette smoking and alcohol consumption, and the prevalence of metabolic syndrome. 8. The presence of metabolic syndrome was found as often in the group of people who claimed that nourish healthy and in those that do not lead a healthy way of eating. Keywords: metabolic syndrome, stable angina pectoris, coronary angiography